Diagnosis and treatment of cardiac amyloidosis: a position statement of the ESC Working Group on Myocardial and Pericardial Diseases. (7th April 2021) - Garcia-Pavia, Pablo; Rapezzi, Claudio; Adler, Yehuda; Arad, Michael; Basso, Cristina; Brucato, Antonio; Burazor, Ivana; Caforio, Alida L P; Damy, Thibaud; Eriksson, Urs; Fontana, Marianna; Gillmore, Julian D; et al.
Abstract: Cardiac amyloidosis is a serious and progressive infiltrative disease that is caused by the deposition of amyloid fibrils at the cardiac level. It can be due to rare genetic variants in the hereditary forms or as a consequence of acquired conditions. Thanks to advances in imaging techniques and the possibility of achieving a non-invasive diagnosis, we now know that cardiac amyloidosis is a more frequent disease than traditionally considered. In this position paper the Working Group on Myocardial and Pericardial Disease proposes an invasive and non-invasive definition of cardiac amyloidosis, addresses clinical scenarios and situations to suspect the condition and proposes a diagnostic algorithm to aid diagnosis. Furthermore, we also review how to monitor and treat cardiac amyloidosis, in an attempt to bridge the gap between the latest advances in the field and clinical practice. Graphical Abstract: